Akselerasi Kinerja Layanan Sekretariat DPRD Melalui Inovasi: Studi Kasus Sekretariat DPRD Kota Medan - Savira, Evi; Savitri, Renny; Ahad, Madya; Hutasoit, Erisda; Simanjuntak, Andres (Research and Development Agency Ministry of Home Affairs, 2022)
Public organizations' outputs are services both inside and outside the organization. Medan Regional Legislative Council Secretariate is one of the regional apparatus organizations (OPD) whose performance output is service to the bureaucracy, which in this case is to members and leaders of the Regional Legislative Council. The service performance of the Medan Regional Legislative Council Secretariate is still considered dissatisfaction, and the Government Agency Performance Accountability Report (LAKIP) scores B. The purpose of this study is to provide an overview of the novelty of the Medan Regional Legislative Council Secretariate in accelerating its performance through a stakeholder satisfaction survey and innovation. This study uses a mixed method of both quantitative and qualitative research methods. The research questions are (1) What innovation acceleration does the Medan Regional Legislative Council Secretariate conduct to achieve organizational performance goals, and how? (2) How does the results of innovation development on the level of satisfaction of stakeholders on the performance of the Medan Regional Legislative Council Secretariate services in 2019-2021? (3) What lessons were learned from efforts to improve performance through surveys and innovations at the Secretariate? This study results from a stakeholder satisfaction survey followed up with four innovations to accelerate the performance of the Medan Regional Legislative Council Secretariate. The results of this study found that the development of these four innovations was not optimal; there was only one innovation that directly impacted organizational performance. Although technocratic studies have been carried out through stakeholder satisfaction surveys and innovation assistance, however, the innovation decisions made in the context of accelerating performance are highly dependent on the competence of human resources and priority activities.